Couples, money, and expectations: negotiating financial management roles to increase relationship satisfaction - Archuleta, Kristy L. (My University, 2013)
How couples handle money has become a popular subject among scholars, practitioners, and the popular press. However, little is known about how finances should be treated within a clinical context. This study examined the financial management roles in which couples participate and their satisfaction level with these roles as well as couples’ communication tactics surrounding money and their impact on relationship and financial satisfaction. Results suggested that having shared goals and values about money were a stronger predictor of relationship satisfaction than were communication strategies. In addition, satisfaction with one’s financial management role participation may be more important than self-reported financial management roles each partner performs. In this study, financial management roles included 19 areas, including responsibilities such as bookkeeping, financial decision-making, and taxes.
Keywords: Financial management roles; Financial satisfaction; Relationship satisfaction; Shared goals and values